2014
DOI: 10.1002/jso.23705
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial to mesenchymal transition might be induced via CD44 isoform switching in colorectal cancer

Abstract: The status of EMT and CD44 is a critical prognostic factor, with CD44 isoform switching a possible trigger for EMT in CRC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 35 publications
2
22
1
Order By: Relevance
“…In a study of colorectal cancer, the standard isoform CD44s seemed to be correlated with EMT, but higher CD44 expression predicted poor survival in that study in contrast to our results in ovarian cancer [26]. …”
Section: Discussioncontrasting
confidence: 96%
“…In a study of colorectal cancer, the standard isoform CD44s seemed to be correlated with EMT, but higher CD44 expression predicted poor survival in that study in contrast to our results in ovarian cancer [26]. …”
Section: Discussioncontrasting
confidence: 96%
“…A switch from CD44v to CD44s is essential for EMT and tumour progression in breast cancer (Brown et al , 2011). Furthermore, the ratio of vimentin/E-cadherin mRNA expression is significantly correlated with the CD44s/CD44v9 ratio in colorectal cancer, indicating that CD44 switching might induce EMT (Mashita et al , 2014). These findings suggest that CD44s confers mesenchymal properties, unlike other CD44-variants, and is associated with metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of E-cadherin was previously shown to be repressed when ZEB1, ZEB2, or Snail bound to the E-box elements of CDH1, which encodes E-cadherin. 8,9) The down-regulated expression of E-cadherin is characterized by the loss of cell-cell adhesion and acquisition of a migratory phenotype. Mashita et al reported that the expression levels of standard CD44 isoform (CD44s) mRNA/variant 9 isoform (CD44v9) mRNA (CD44s/CD44v9) ratio were higher in the cells of mesenchymal phenotype than those of epithelial phenotype.…”
mentioning
confidence: 99%